Popular religion and ethnicity: The indigenous population of colonial Lima - Gareis, Iris (1992)
The life of the indigenous people in the Viceroyalty of Peru is usually associated with issues such as the dissolution of the native population, forced labor in the mines or the misery that resulted from the encomienda system, to cite a few examples. The investigations have preferably considered the situation of the indigenous population in rural areas, while the indigenous people who populated urban centers have so far received very little study. Only in the last decade have some articles been published that address this interesting problem.